The Effect of Financial Inclusion on Broiler Farmers Income (Census in Pangandaran Regency) - Rahmadini, Anggita; Firman, Achmad; Fitriani, Anita (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2022)
ABSTRACT The world of broiler farming, especially farmers with small scale businesses, is still faced with business capital problems. Pangandaran Regency really feels the impact of this capital problem which is reinforced by the Central Bureau of Statistics data that the population of broiler chickens in Pangandaran Regency in 2016 was 239,419 heads. This figure is still relatively small compared to other regencies or cities such as Ciamis Regency with a population of 14,605,475 individuals. The research was carried out in June-August 2021 in six sub-districts in Pangandaran Regency, namely Mangunjaya, Padaherang, Sidamulih, Parigi, Lkaplancar, Cigugur. The purpose of this study is to analyze what are the financial inclusion factors that affect the income of broiler breeders in Pangandaran Regency, what are the financial inclusion factors that significantly affect the income of broiler breeders in Pangandaran Regency. The census was used as a sampling method because the population of breeders was less than 100 people. The results obtained are that financial education has a significant effect on the income of broiler farmers in Pangandaran Regency, intermediation facilities and distribution channels, financial services in the government sector, consumer protection has a significant effect on the income of broiler farmers in Pangandaran Regency. Keywords: Financial Inclusion, Farmer Income, Broiler Chicken